A randomized pilot study on self-management in head and neck lymphedema - McLaughlin, Tess; Broadhurst, Jane; Harris, Courtenay; McGarry, Sharon; Keesing, Sharon (2020)
Background: The purpose of this pilot trial was to determine the feasibility of a self‐managed lymphedema randomized control trial to test the effectiveness of a head and neck‐specific exercise protocol.